The Adoption of an Open Textbook in a Large Physics Course: An Analysis of Cost, Outcomes, Use, and Perceptions - Hendricks, Christina; Reinsberg, Stefan A.; Rieger, Georg W (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Assigning open textbooks in college and university courses can help students save money on increasingly expensive commercial textbooks, and recent research shows that this savings can often be achieved with little to no sacrifice in textbook quality or student learning outcomes. We add to this body of research by examining the use of an open textbook in an introductory physics course at a large research university in Canada that enrols approximately 800-900 students per year. In this course, the instructors revised an open textbook and combined it with other learning resources onto a single website, whereas more than one source of learning materials was used previously. We used the COUP framework to structure our analysis, focusing on cost, outcomes, use, and perceptions in relation to the open textbook assigned in the course. Through the use of a survey of students and data about student learning outcomes in the form of final exam and course grades, and shifts on the pre-/post- Colorado Learning Attitudes about Science Survey, we show that student savings by moving to an open textbook were accompanied by little change in learning outcomes. We also show that the vast majority of survey respondents perceived the open textbook to be of the same or better quality than commercial textbooks used in their other courses. Further, many of them appreciated the fact that the textbook was customized to this particular course—which is made possible by the use of a textbook with an open license.